Trade and domestic production networks - Felix Tintelnot; Ayumu Ken Kikkawa; Magne Mogstad; Emmanuel Dhyne (National Bank of Belgium, 2018)
We use Belgian data with information on domestic firm-to-firm sales and foreign trade transactions to study how international trade affects firm efficiency and real wages. The data allow us to accurately construct the domestic production network of the Belgian economy, revealing several new empirical facts about firms' indirect exposure to foreign trade through their domestic suppliers and buyers. We use this data to develop and estimate models of domestic production networks and international trade. We first consider a model of trade with an exogenous network structure, which gives analytical solutions for the effects of a change in the price of foreign goods on firms' production costs and real wages. To examine how gains-from-trade calculations change if buyer-supplier links are allowed to form or break in response to changes in the price of foreign goods, we next develop a model of trade with endogenous network formation. We take both models to the data and compare the empirical results to those we obtain using existing approaches. This comparison highlights the relevance of data on and modeling of domestic production networks in studies of international trade.
Keywords: F14; L14; 330; Production Networks; Network formation; Indirect imports and exports; Gains from trade; Exportwirtschaft; Unternehmensnetzwerk; Außenhandel; Stückkosten; Außenhandelsgewinn; Belgien